INFORMATION SOURCES FOR EFFICIENT OPERATION OF CONTROLLING FUNCTION IN THE COMPANY - Jeličić, Dalibor; Bojanić, Ranko; Vujičić, Slađana (ACADEMIC REVIEW, 2022)
Controlling in the company should be primarily the most important source of information used for successful business operations. In addition, controlling should be also a place of planning and analysis, business decision consultant, and coordinator and integrator of business functions. It is all based on the information it possesses. What is the main source of the information it needs? This paper attempts to show the most important sources of information received by controlling from departments of finance and accounting, sales, planning and analysis, production, marketing, procurement and information gathered from the business environment of the company. The survey covered 157 respondents working in 14 companies operating in the beverage industry and grouped in two sub-samples: in the first sub-sample companies were grouped based on their ownership structure, in the second based on their size. Only companies grouped according to their size, i.e. the number of employees will be discussed in this paper given that results obtained in the research referring to companies which were grouped according to their ownership structure have shown low statistical significance.